A Business Proposal: A Study of Netizens' Perceptions of the Cancel Culture Phenomenon in the Film Industry - Sarifhatul Aini Yuliyus Putri; Siti Khumayah; Aghnia Dian Lestari (Journal Of Social Science (JoSS), 2026)
Social media has become a digital public sphere that plays a significant role in shaping public opinion and social sanctions against public figures. One emerging phenomenon is "Cancel Culture," which refers to the collective action of the public to withdraw support from individuals perceived to have committed wrongdoing. In the film industry, an actor's behavior on social media can significantly impact how the public perceives the films in which they star. This research aims to analyze the relationship between actors' behavior on social media, the emergence of the "Cancel Culture" phenomenon, and public reception of the Indonesian version of the film "A Business Proposal". This reserch employs a descriptive qualitative approach using data collection techniques such as social media observation, in-depth interviews, and documentation. This research employs Stuart Hall's Reception Theory to identify the audience's interpretive positions (dominant, negotiation, and opposition) and to understand Cancel Culture as a mechanism of social sanction in the digital space. The results indicate that audiences actively construct meaning regarding actors' behaviors, leading to varied receptions including acceptance, negotiation, and rejection toward Cancel Culture practices. These findings confirm that social media functions not only as a communication medium but also as an arena for shaping public opinion and exercising social control within the film industry.